Unveiling The Impact of Face Consciousness and Acquisition Centrality on Counterfeit Buying Intention: The Mediation and Moderation Model - Aprilliani, Shifa; Syahbandi; Fitriana, Ana; Barkah; Listiana, Erna (Ilomata International Journal of Management, 2025)
This research explores how face consciousness and acquisition centrality influence intentions to purchase counterfeit goods, with counterfeit attitude serving as a mediator and perceived anonymity as a moderator. This study utilized a survey method and included 284 Indonesian customers. Data was evaluated using SmartPLS software and Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that face consciousness has a negative effect on counterfeit attitudes (β = -0.180, p < 0.003), while acquisition centrality has a positive impact (β = 0.802, p < 0.000). Additionally, counterfeit attitude mediates the relationship between these factors and buying intentions. Perceived anonymity moderates these relationships by weakening the connection between face consciousness and counterfeit attitude (β = -0.114, p < 0.020) but enhancing the link between acquisition centrality and counterfeit attitude (β = 0.326, p < 0.000). These findings show that social concerns and materialistic values strongly influence attitudes and intentions toward counterfeit products. Practical consequences include targeted consumer education to diminish the counterfeit appeal and promote the value of genuine products. Policymakers are asked to tighten restrictions and raise awareness of the economic and ethical consequences of counterfeit products. Marketers can use these data to differentiate their products and appeal to consumers' demand for authenticity.